2010
DOI: 10.1128/jcm.01271-10
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Susceptibility of the Yeast Pathogen Cryptococcus to Fluconazole and Other Azoles Varies with Molecular Genotype

Abstract: Cryptococcosis is primarily caused by Cryptococcus neoformans and Cryptococcus gattii. These two pathogenic species each divide into four distinct molecular genotypes. In this study, we examined whether genotype influenced susceptibility to antifungal drugs used to treat cryptococcosis using the broth microdilution method described by the Clinical and Laboratory Standards Institute. C. gattii isolates belonging to molecular genotype VGII had significantly higher MIC values for flucytosine and all azole antifun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
66
1
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(75 citation statements)
references
References 47 publications
7
66
1
1
Order By: Relevance
“…Following their analysis of susceptibility profiles of C. gattii genotypes, Chong et al [49] reported higher MIC values for fluconazole (≥ 64 µg/mL) against C. gattii VGII than against C. gattii VGIII and VGI [48]. Iqbal et al [50] reported differences in the susceptibility profiles of the molecular types of C. gattii, having determined higher MIC values for the VGII subtypes than the VGI and VGIII subtypes.…”
Section: Discussionmentioning
confidence: 99%
“…Following their analysis of susceptibility profiles of C. gattii genotypes, Chong et al [49] reported higher MIC values for fluconazole (≥ 64 µg/mL) against C. gattii VGII than against C. gattii VGIII and VGI [48]. Iqbal et al [50] reported differences in the susceptibility profiles of the molecular types of C. gattii, having determined higher MIC values for the VGII subtypes than the VGI and VGIII subtypes.…”
Section: Discussionmentioning
confidence: 99%
“…Recent epidemiological studies observed that isolates collected from different geographic regions have altered susceptibilities to fluconazole, as emerging resistance was documented among isolates from the Asia-Pa-cific, Africa/Middle East, and Latin America regions but not among isolates from Europe or North America (458). Furthermore, the molecular genotype of cryptococcal species influences fluconazole susceptibility, with genotype VGII of C. gattii and genotype VNI of C. neoformans displaying elevated fluconazole MICs compared to those of other genotypes within their respective species (102). Finally, it was also found that after initial treatment with fluconazole, relapses of cryptococcal meningitis tended to be associated with elevated levels of fluconazole resistance (55).…”
Section: Cryptococcus Neoformans Drug Resistance: the Azolesmentioning
confidence: 99%
“…The results of a number of studies have suggested that differences in in vitro drug susceptibility are correlated with different Cryptococcus species and molecular types (19)(20)(21)(22)(23). MICs of all azoles, particularly fluconazole, appear to be higher for molecular type VGII isolates than for other C. gattii molecular types, primarily VGI, and C. neoformans (19,21,23).…”
mentioning
confidence: 97%
“…MICs of all azoles, particularly fluconazole, appear to be higher for molecular type VGII isolates than for other C. gattii molecular types, primarily VGI, and C. neoformans (19,21,23). There is also growing evidence that antifungal drug susceptibility may vary between geographical locations for the same molecular type (19,21,24).…”
mentioning
confidence: 98%